Gender And Language Use - Rahmi, Rahmi (Intelektualita, 2015)
Gender issue which is a social construction according to culture and belief has been studied in language use since 1970s. When a language is expressed, it is considered that men and women use different expressions. There are some theories that have been proposed related to this concern such as the Deficit Theory, the Dominance Theory, the Radical Theory, the Difference Theory and the Reformist Theory. Gender in language use which is one of discussions in pragmatics consists of some terminologies that are used to represent men and women directly in a language, those are Grammatical Gender, Lexical Gender, Referential Gender and Social Gender. Furthermore, lots of stereotypes found express more negative opinions related to the language of women compared to men. Some factors affect gendered use of linguistic varieties like work and marriage opportunities, industrialization and urbanization, and social network. In education in particular, three areas important to be focused on, those are subject matter, teaching and learning process and classroom material.